Koli father and son from Khar Danda Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
Rahul Bhalia, a 26-year-old resident of Khar Danda Koliwada, a fishing village, assists his father, Rakesh Bhalia, in running fishing operations. Rahul and his father operate a small boat instead of working on larger trawlers. While trawlers offer safety and extended time at sea, they come with high operational costs. The father-son duo's preference for a small boat allows them to operate at lower costs.